Effect of CO2/H2S and Applied Stress on Corrosion Behavior of 15Cr Tubing in Oil Field Environment - Xuehui Zhao; Wei Huang; Guoping Li; Yaorong Feng; Jianxun Zhang (Metals, 2020)
The corrosion behavior of a 15Cr-6Ni-2Mo martensitic stainless steel (15Cr stainless steel) in a CO2/H2S environment was investigated by conducting high-temperature/high-pressure immersion tests combined with scanning electron microscopy and metallographic microscopy. The presence of H2S decreased the corrosion resistance of the 15Cr tubing steel. The critical H2S partial pressure (PH2S) for stress corrosion cracking in the 15Cr tubing steel in the simulated oil field environment with a CO2 partial pressure of 4 MPa and an applied stress of 80% σs was identified. The 15Cr tubing steel mainly suffered uniform corrosion with no pitting and cracking when the PH2S was below 0.5 MPa. When the PH2S increased to 1 MPa and the test temperature was 150 °C, the pitting and cracking sensitivity increased. The stress corrosion cracking at a higher PH2S is attributed to the sulfide-induced brittle fracture.